(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article presents the results of the use of innovative technologies in overcoming violations of the lexical and grammatical structure of speech in older preschool children with generalized speech impairment level III. The prerequisites for the use of innovative technologies in speech therapy work are revealed. The content of the speech therapist’s work on the use of innovative technologies in overcoming violations of the lexical and grammatical structure of speech in older preschool children with Generalized speech impairment level III has been determined.